"My First Victim Was a Hurling Player . . . ": Sport in the Lives of Northern Ireland's Political Prisoners. (August 2016) - Bairner, Alan
Much of the recent literature on sport, political violence, and terrorism has been focused on security issues and, more critically, their potentially damaging implications for civil liberties. Far less attention, however, has been paid to the place of sport in the lives of the so-called terrorists themselves. This article draws heavily on personal experience of interaction with loyalist and republican prisoners in the Maze between March 1996 and October 1999. The main focus of the article is on the ways in which these prisoners talked about and related to sport and the insights that discussions with them offered in terms of their wider political views. Sport was never dismissed by any of the prisoners I met as being of secondary importance to other matters—a diversion from the real world of politics. In fact, as our discussions revealed, politics was often presented as being intimately bound up with and embodied in sport cultures. On the other hand, their interest in sport also highlighted the fact that these were rather ordinary men, some of whom had shown themselves to be capable of committing seemingly extraordinary crimes.